Energy and spectral efficiency optimization in multiuser massive MIMO Comunications systems. - Marinello Filho, José Carlos (2018)
Massive MIMO communication systems have been highlighted as the main technology for physical layer of next generation communication standards, like 5G. While conventional communication between BS and its covered users is performed in orthogonal time-frequency resources, the improved interuser interference mitigation capability provided by the large number of BS antennas enables the BS to communicate with several users in the same time-frequency resource. This better usage of available but scarce spectrum elevates the spectral efficiency to very appreciable levels, and has a similar effect on energy efficiency, since the transmit power is not increased. On the other hand, if the objective is to provide a target performance for the users, the required transmit power in both direct and reverse links can be made inversely proportional to the number of BS antennas employed. In this Doctoral Thesis, several important aspects of massive MIMO systems are systematically investigated aiming to improve their energy and spectral efficiencies. We can enumerate our main contributions as follows. Considering a cellular massive MIMO network, we proposed an optimized assignment policy of training sequences to the users, which is then combined with suitable power control algorithms. We have also investigated the adoption of alternative waveforms in this scenario, such as single-carrier transmission, in order to overcome the issues of conventional OFDM. Our contributions in this topic are to derive analytical performance expressions for a time-domain single-carrier equalizer taking advantage of the large number of BS antennas, and to evaluate and compare the total energy efficiency of OFDM versus single-carrier massive MIMO systems. Finally, considering crowded massive MIMO networks, composed by both human users as well as machine-type communication devices, we proposed an improved random access protocol aiming to decrease the average number of access attempts for the users and decreasing the probability of failed access attempts.